2015
DOI: 10.5901/mjss.2015.v6n1s1p665
|View full text |Cite
|
Sign up to set email alerts
|

A Micro-level Analysis of the Effect of Remittances on Health Expenditures: Evidence from Albania

Abstract: Using household survey data for Albania, the paper investigates the effect of remittances on health capital accumulation. Total expenditure is divided into two categories: expenditure on medicines and expenditure on visits and laboratory services. The estimation is presented for two separate sub groups, rural and urban area. In the paper both instrumental variable and propensity score matching are used to give answer to the research question about the impact of remittances in the health capital investment.The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 15 publications
(1 reference statement)
0
8
0
1
Order By: Relevance
“…This problem was more common in the studies that analyzed the effect of remittances on health expenditure or some health-related outcomes. The strategies most used to avoid biased estimations were the instrumental variables (12,27,28,29,30,31,32,33,34), estimation through the methods Propensity Score Matching and the models of difference in differences (35,36), as well as the use of estimators of fixed effects, in the case of the models with panel data (37,38,39).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This problem was more common in the studies that analyzed the effect of remittances on health expenditure or some health-related outcomes. The strategies most used to avoid biased estimations were the instrumental variables (12,27,28,29,30,31,32,33,34), estimation through the methods Propensity Score Matching and the models of difference in differences (35,36), as well as the use of estimators of fixed effects, in the case of the models with panel data (37,38,39).…”
Section: Resultsmentioning
confidence: 99%
“…There is as well an asociation between receiving remittances and the decrease of fertility rates (27,34,74) and child mortality (7,12,34,49). Regarding the general health condition, receiving remittances decreases the probability of suffering from a chronic or sudden disease (36) and improves health outcomes, including the children's (7,8,75).…”
Section: Effect Of Transfers On Health Conditions Of the Household Inmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 3 shows the review of the effects of remittances on health expenditure in Albania, an analysis of the impact of remittances on health expenditures showed that households receiving remittances increased their health expenditures on drugs and other health-related services such as medical visits and laboratory services. [6] The impact was significant for households in rural areas because the total expenditures on drugs increased by approximately $86.27. The findings of the study reveal that remittances have a positive impact on the expenditure for medical visits and laboratory services.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The findings of the study reveal that remittances have a positive impact on the expenditure for medical visits and laboratory services. [6] In Mexico, data from a nationally representative survey carried out by the Mexican statistical institute showed that remittances increased health expenditures for both low-income households and rich households. [18] High-income households receiving $5.25 increment in remittance increased expenditures on health by $0.37.…”
Section: Study Characteristicsmentioning
confidence: 99%